85 Parent and youth experiences of emergency department care for suspected long bone fractures in children. (19th August 2020) - Gaucher, Nathalie; Trottier, Evelyne D; Ridha, Zainab; Simard, Francois; Duran, Brenda; Pinard, Celine; Larose, Guylaine; D'Arsenault, Michael; Angelo, Antonio; Janvier, Annie
Abstract: Background: Long bone fractures are a frequent reason for visits to the pediatric emergency department (ED) where patients obtain the definitive care they require. Youth are rarely involved in quality assessment and improvement initiatives. Objectives: To describe parent and youth experiences of their ED care for suspected long bone fractures. Design/Methods: This prospective survey study of parents/youth consulting a tertiary care pediatric ED used surveys co-constructed by ED clinicians and parent partners. English/French speaking patients aged 10 to 18 years old with suspected long-bone fracture at triage – and their parents – were eligible to complete the survey during their ED stay. Electronic surveys were developed for parents and youth and pre-tested with 12 youth and 14 parents. Descriptive data was generated using SPSS v.25 (IBM Inc.). Results: Three hundred surveys were distributed to eligible participants from March 2018 to June 2019 and 249 surveys were completed (148 parents, 101 youth). At least one member from 189 families completed a survey. Parents and youth participants had median ages of 44 and 12 years old, respectively. Most patients (98%) had a radiograph as part of their work-up, usually in the ED (76%); Twenty-seven percent were referred with radiographs. Most families (61%) received a diagnosis of long-bone fracture and were referred to orthopaedics for outpatient follow-up. Families' median length of stay was 4h08min (range 43 min-14h30min). Parents (88mm) and youth (81mm) reported high median satisfaction with their overall ED care on 100 mm visual analog scales. Most parents (81%) and youth (75%) reported receiving just enough information from ED staff, though only half (50%) of the parents received information on how to care for their child at home. More than 90% of parents believed that the ED team treated their child's pain. Eighty-one percent of youth reported that pain was treated sufficiently although 63% believed it had been treated quickly. Most parents (56%) and youth (72%) reported their ED stay was longer than anticipated; parents' perceptions did not correlate with ED length of stay on logistic regression (p=0.014), while youth's did (p=0.009). Few parents (33%) or youth (32%) reported receiving regular information on ED wait times. Conclusion: Parent and youth perspectives of their ED care are complementary, and both should be considered in patient-oriented quality improvement initiatives.